Answer:
2
Explanation:
Simplify the following:
(1 + 1/9)/(5/9)
Multiply the numerator of (1 + 1/9)/(5/9) by the reciprocal of the denominator. (1 + 1/9)/(5/9) = ((1 + 1/9)×9)/5:
((1 + 1/9)×9)/5
Put 1 + 1/9 over the common denominator 9. 1 + 1/9 = 9/9 + 1/9:
(9/9 + 1/9 9)/5
9/9 + 1/9 = (9 + 1)/9:
((9 + 1)/9×9)/5
9 + 1 = 10:
(10/9×9)/5
10/9×9 = (10×9)/9:
((10×9)/9)/5
((10×9)/9)/5 = (10×9)/(9×5):
(10×9)/(9×5)
(10×9)/(9×5) = 9/9×10/5 = 10/5:
10/5
The gcd of 10 and 5 is 5, so 10/5 = (5×2)/(5×1) = 5/5×2 = 2:
Answer: 2